Babymouse. [3], Beach babe - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2006)
A graphic novel about the summertime adventures of Babymouse, who tries surfing and snorkeling for the first time and learns a lesson when she wishes for someone "cooler" than her little brother, Squeak, to play with.
3.2
3-6.
3-6
Keywords: Animals -- Comic books, strips, etc -- Fiction; Beaches -- Comic books, strips, etc -- Fiction; Brothers and sisters -- Comic books, strips, etc -- Fiction; Mice -- Comic books, strips, etc -- Fiction; Animals -- Fiction; Beaches -- Fiction; Brothers and sisters -- Fiction; Cartoons and comics; Mice -- Fiction; Animals -- Comic books, strips, etc -- Fiction; Beaches -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Mice -- Comic books, strips, etc -- Fiction; Siblings -- Comic books, strips, etc -- Fiction; Graphic novels